Testing methods for grout materials

JP2026165355APending Publication Date: 2026-10-14KAJIMA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025057697
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、グラウト材注入前の品質管理試験として、グラウト材のブリーディングや脱泡を簡易かつ正確に観察又は測定することができるとともに、グラウト材の体積変化を求めることができる試験方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165355000001_ABST
    Figure 2026165355000001_ABST
Patent Text Reader

Abstract

This invention provides a test method that allows for simple and accurate observation or measurement of bleeding and degassing of grout material, as well as determination of volume changes, as a quality control test before grout injection. [Solution] A test method for determining the volume change of grout material, wherein a liquid 3 having a specific gravity less than water and being incompatible with water is layered on top of grout material 2 before hardening, which is filled in a columnar container 1, and the change over time of at least one of the following: the height position of the upper surface of the grout material 2, the height position of the upper or lower surface of the liquid 3, and the height position of the upper surface or layer thickness of bleeding water 4 if bleeding occurs. The liquid 3 suppresses the drying of the grout material 2 by contact with air. The bleeding water 4 accumulates between the grout material 2 and the liquid 3. Bubbles removed from the grout material 2 can be visually confirmed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a test method for a grout material. Background Art

[0002] A grout material is a liquid or paste-like material used in architectural and civil engineering works, and is used to fill gaps and cavities in building structures and soil. By injecting the grout material, it is possible to join structures together, increase the strength of structures, prevent water leakage, and stabilize the ground.

[0003] In the construction work using a grout material, a concern arises that the volume of the grout material decreases over time after injection due to various causes, impairing the performance of the grout material. As an example of countermeasures, at construction sites, an excessive volume of grout material is used in anticipation of the volume reduction of the grout material, the grout material is allowed to set while overflowing from the injection port, and the excess grout material is removed after hardening (for example, refer to Patent Document 1 regarding the injection of grout material into joints between precast concrete members).

[0004] One of the causes of the volume reduction of the grout material is bleeding. Conventionally, a method for measuring the bleeding rate and volume change rate of a grout material is known (Non-Patent Document 1), by which the degree of volume reduction of the grout material can be known in advance.

[0005] Further, one of the causes of the volume reduction of the grout material is that air entrained during mixing when the grout material is prepared from powder and water is defoamed after the grout material is injected. If the grout material hardens while the defoamed air bubbles remain in the grout material, cavities will be formed in those portions, degrading the construction quality. Therefore, it is desirable to avoid using a grout material with a large defoaming amount. Prior Art Documents Patent Documents

[0006] [Patent Document 1] Patent No. 7145809 [Non-patent literature]

[0007] [Non-Patent Document 1] Compiled by the Japan Society of Civil Engineers, established in 2013, Standard Specifications for Concrete [Standards Section], Japan Society of Civil Engineers Standards and Related Standards, "F. Fresh Concrete 21. Test Method for Bleeding Rate and Volume Change Rate of PC Grout (Vertical Pipe Method) (Draft) (JSCE-F535-2012)" [Overview of the project] [Problems that the invention aims to solve]

[0008] When checking the volume change of grout material in advance at the construction site, the measurement method described in Non-Patent Document 1 requires large and cumbersome equipment, including an injection pump, and there is a risk that the exposed surface may dry out during prolonged measurement, making accurate measurement impossible. Furthermore, it is uncertain whether degassing can be observed or accurately measured using the measurement method described in Non-Patent Document 1. Therefore, the measurement method described in Non-Patent Document 1 is not suitable as a quality control test before grout material injection at the construction site.

[0009] Therefore, the present invention aims to provide a test method that allows for easy and accurate observation or measurement of bleeding and degassing of grout material, as well as determination of volume changes of grout material, as a quality control test before grout material injection. [Means for solving the problem]

[0010] The present invention provides a test method for determining the volume change of grout material, wherein a liquid with a specific gravity less than water and that is incompatible with water is layered on top of the grout material before hardening, which is filled in a columnar container, and the change over time of at least one of the following: the height position of the top surface of the grout material, the height position of the top or bottom surface of the liquid, and the height position of the top surface of the bleeding water or the thickness of the layer if bleeding occurs.

[0011] In this test method, a liquid with a specific gravity lower than water and that is incompatible with water is layered on top of the grout material, thus preventing the grout material from drying out due to exposure to air during the test. Furthermore, if bleeding occurs, the bleeding water accumulates between the grout material and the liquid, making it easy to determine the degree of bleeding. In addition, air bubbles removed from the grout material can be visually confirmed, making it easy to determine the degree of degassing. By performing this test method at the construction site before application, the degree of bleeding and degassing can be quickly determined, and the degree of volume reduction after application of this grout material can be predicted.

[0012] Furthermore, in this invention, the above test method may be carried out, and based on the results, the test method may be carried out again by changing at least one of the following: the mixing time of the grout material, the setting time of the grout material, the amount of water added, and the materials of the grout material. This makes it possible to find a grout material that reduces the volume decrease after construction.

[0013] In the present invention, the container preferably has a cylindrical shape in the portion for filling with grout material, with an inner diameter of 50 mm to 150 mm, and a height of 297 mm to 303 mm for the filled grout material. A container that meets these criteria is of a convenient size for use as a device at a grout material construction site and is particularly easy to handle.

[0014] In the present invention, it is preferable that the grout material contains an expansive material that does not generate gas. This also helps to suppress long-term shrinkage of the grout material. [Effects of the Invention]

[0015] According to the present invention, a test method is provided that allows for the simple and accurate observation or measurement of bleeding and degassing of grout material, as well as the determination of volume changes of grout material, as a quality control test before grout material injection. [Brief explanation of the drawing]

[0016] [Figure 1] Both (A) and (B) are diagrams showing a test method that is one embodiment of the present invention. [Figure 2] This is a graph showing the results of a confirmation test for the readability of volume change. [Figure 3] Both (A) and (B) are photographs showing the state of bleeding and scale reading. [Figure 4] This is a graph showing the results of Test Examples 1 and 2. [Modes for Carrying Out the Invention]

[0017] The present invention is a test method that can avoid the use of grout materials with a high possibility of causing construction defects by confirming in advance the volume change that occurs after the construction of the grout material during the construction of the grout material.

[0018] A volume decrease is usually observed as the volume change of grout material after construction. Possible causes of the volume decrease include bleeding, defoaming, and shrinkage of the grout material (shrinkage due to drying, and autogenous shrinkage accompanying hardening). Among these, bleeding and defoaming are problematic in the short term, which is the period during which the grout material sets, and the shrinkage of the grout material is problematic in the long term from after setting to hardening where sufficient strength development occurs.

[0019] In the present invention, focusing on bleeding and defoaming that occur in the short term, these are observed or measured simply and accurately, and the volume change of the grout material is determined. Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the drawings.

[0020] <Test Method> In the test method of the present embodiment, a liquid having a specific gravity lower than that of water and being incompatible with water (hereinafter referred to as "layered liquid") is layered above the uncured grout material filled in a columnar container with an open top. Here, "incompatible with water" does not mean being completely incompatible with water, but means that the solubility of the layered liquid in water is insoluble (for example, 0 mg / L to 1000 mg / L, 0 mg / L to 500 mg / L, or 0 mg / L to 100 mg / L).

[0021] As for the type of grout material that is the subject of the test method of the present embodiment, the effect of the present embodiment is particularly exhibited when it is a cement-based material that is prone to bleeding during setting or air entrainment during preparation. Among cement-based materials, non-shrink mortar is preferred.

[0022] The grout material may contain various admixtures to adapt to specific construction conditions and required performances. Examples of the admixture include a water reducing agent that can reduce the amount of water used while improving the fluidity of the grout material, a fluidizing agent for improving the fluidity of the grout material, an expanding agent for suppressing the shrinkage of the grout material and stabilizing the volume after curing, a setting retarder that extends the setting time and enables construction over a long period of time, and the like. From the viewpoint of suppressing long-term shrinkage of the grout material (shrinkage due to drying and autogenous shrinkage accompanying curing), it is preferable to contain an expanding agent.

[0023] As the expanding agent, an expanding agent that does not generate gas is preferable, and an expanding agent that produces ettringite or calcium hydroxide is preferable.

[0024] Examples of the type of layered liquid include machine oil, fatty oils (corn oil, sesame oil, olive oil, etc.), and the like.

[0025] First, prepare a columnar container with an open top. If the columnar container has an asymmetrical shape, the volume reduction of the grout material tends to be uneven. Also, if it does not have a certain height, it is difficult to measure the volume change. Furthermore, if it does not have a certain thickness, it is difficult for air bubbles generated during degassing to escape. From these viewpoints, it is preferable that the portion of the columnar container that is filled with grout material is cylindrical, the inner diameter of the cylinder is preferably 50 mm to 150 mm, and the length is preferably such that the height of the filled grout material is 297 mm to 303 mm. Moreover, a container that satisfies these conditions is a convenient size for use as a device at a grout material construction site and is particularly easy to handle. The material of the container is preferably colorless and transparent, and preferably made of glass or resin.

[0026] To conduct the test, the grout material must first be prepared. Generally, water is added to the powdered grout material and mixed to prepare the grout material before it hardens. After mixing, the grout material is either left to stand or filled into a columnar container without waiting. The top surface of the filled grout material is adjusted to be flat, and then the lamination liquid is immediately applied to the top surface.

[0027] The items to be measured are as follows: (1) Height position of the top surface of the grout material (2) Height position of the upper or lower surface of the layered liquid (3) Height position or layer thickness of the upper surface of bleeding water when bleeding occurs At least one of these will be the target of measurement. First, measure immediately after the layering liquid is layered, and then record the change over time. Recording may be done at 10-minute intervals, 15-minute intervals, or 30-minute intervals. A ruler with a 1 mm scale will be used for measurement.

[0028] Figure 1 shows the state of the test specimen immediately after filling with grout material (referred to as "initial") and after a certain amount of time has passed (referred to as "after time has passed"). This is an example where bleeding occurred. Initially, only grout material 2 and lamination liquid 3 were present in container 1 (Figure 1(A)), but after time has passed, the grout material has set, and in addition to grout material 2 and lamination liquid 3, bleeding water 4 is present in container 1 (Figure 1(B)). Also, after time has passed, the total volume of contents in container 1 has decreased. The grout material then sets further and hardens.

[0029] The reason for the decrease in the total volume of contents inside container 1 is degassing, and the thickness [L] representing the amount of degassed air is expressed by the following formula. The thickness [L] indicating the amount of degassed air = initial grout thickness [G1] - (grout thickness after time elapsed [G2] + bleeding water thickness [W]) Furthermore, if evaporation of the lamination liquid and absorption into the grout material can be ignored, the difference in the total height of the contents inside container 1 directly corresponds to the thickness [L], which represents the amount of air removed.

[0030] If the amount of bleeding water is too large, it will hinder the function of the grout material, and if the amount of degassing is too large, air bubbles will remain after hardening, reducing the quality of the work. Therefore, it is desirable to reduce these factors. Accordingly, based on the above test results, it is preferable to repeat the above test method by changing at least one of the following: the mixing time of the grout material, the setting time of the grout material, the amount of water added, and the material of the grout material. Specifically, the amount of degassing can be reduced by reducing the mixing time of the grout material or by increasing the setting time (including reducing air bubbles by allowing time to pass through circulation by pumping). In addition, the amount of bleeding water can be reduced by reducing the amount of water added. In addition, the grout material itself can be changed to a different material.

[0031] In the test method described above, a liquid with a specific gravity lower than water and that is incompatible with water is layered on top of the grout material, thus preventing the grout material from drying out due to exposure to air during the test. Furthermore, if bleeding occurs, the bleeding water accumulates between the grout material and the liquid, making it easy to determine the degree of bleeding. In addition, air bubbles removed from the grout material can be visually confirmed, making it easy to determine the degree of degassing. By performing this test method at the construction site before construction, the degree of bleeding and degassing can be quickly determined, and the degree of volume reduction after construction if this grout material is used can be predicted.

[0032] Furthermore, in the above test method, after performing the test method, at least one of the following can be changed based on the results: the mixing time of the grout material, the setting time of the grout material, the amount of water added, and the materials of the grout material, and the test method can be performed again. This makes it possible to find a grout material that exhibits less volume reduction after construction. Therefore, the test method of this embodiment can be implemented as a quality control test before grout material injection at the construction site.

[0033] The use of a layering liquid in the above test method offers the following advantages: (a) There are various factors that cause changes in the volume of grout material, but the lamination liquid prevents the grout material from coming into contact with air and drying, thus eliminating the possibility of volume reduction due to drying shrinkage of the grout. (i) The layered liquid eliminates the possibility of bleeding water reduction due to drying, thus increasing the reliability of the bleeding water measurement. (c) Since the degassed bubbles pass through the layer of the laminated liquid, the amount of degassing is easy to observe visually. When degassing, if the unburned carbon components, which have a lower specific gravity, adhere to the bubbles and float to the surface, these accumulate on the upper surface of the laminated liquid, making it even easier to observe the degree of degassing. (e) Accurate measurement of volume reduction due to degassing is possible. When there is no lamination liquid, when the grout material comes into contact with air, calcium ions in the grout material react with oxygen in the air to produce calcium carbonate, which forms a thin film on the surface of the grout material. This thin film acts as a lid for air bubbles that are trying to degas, preventing them from escaping. Furthermore, the amount and rate of formation of this calcium carbonate thin film are affected by humidity and temperature, which makes measurement difficult.

[0034] <Examples of application> One example of an application for grout material to which the above test method applies is the injection of grout material into joints between precast concrete structures to join them together. Since joints are narrow spaces, the performance of the grout material is affected not only by the chemical components of the grout material itself, but also by the effects of air bubbles and bleeding water that occur over time after injection, as well as environmental factors at the construction site such as temperature, humidity, and heat radiation. In other words, if a large amount of air bubbles and bleeding water are generated and remain in the grout material, the performance of the grout material will be impaired. Furthermore, test results obtained in a laboratory are not necessarily reproducible at a construction site with different environmental conditions.

[0035] The above testing method allows for easy and accurate observation or measurement of bleeding and degassing of grout material at the construction site. Based on the results, bleeding and degassing during construction (and consequently, changes in the volume of the grout material) can be predicted, and measures to reduce these issues can be implemented immediately.

[0036] Furthermore, long-term drying shrinkage and auto-shrinkage can be addressed by applying a primer or similar material to the grout filling area in advance to prevent moisture in the grout from being absorbed by the precast concrete, or by adding an expansive agent to the grout.

[0037] Although preferred embodiments of the present invention have been described above, the present invention is not limited in any way to the above embodiments. [Examples]

[0038] The present invention will be explained in more detail below with reference to test examples. However, the present invention is not limited to the following test examples.

[0039] <Materials used> Grout material A: A mixture of S-Saver G (non-shrink mortar) manufactured by Nippon Steel Blast Furnace Cement Co., Ltd. Grout material B... This is made by adding more water than the standard amount to Nippon Steel Blast Furnace Cement's S-Saver G (non-shrink mortar) and mixing it to induce bleeding. Machine oil... Mineral oil, AZ Corporation machine oil (ISO VG 46) Acrylic tube…A cylindrical acrylic tube with an inner diameter of 74 mm and a length of 320 mm, with one end sealed with a metal plate. The acrylic tube is erected on a stand with the metal plate as the base. A horizontal line was drawn on the outer surface of the acrylic tube at the height to which the grout material will be filled (300 mm from the base). Using this line as a reference line, a ruler (minimum unit 1 mm) was attached vertically to the outer surface of the acrylic tube so that the positional change of the top surface of the grout material in the height direction could be seen.

[0040] <Test to confirm readability of volume change> Freshly mixed grout material A was filled into an acrylic tube erected on a stand, up to the reference line, through the opening at the top. Machine oil was then layered on top of grout material A (layer thickness 10 mm). Subsequently, changes in the height of the top surface of grout material A and the top surface of the machine oil were recorded every 15 minutes. As time progressed, degassing and bleeding were observed. From the point when bleeding occurred, the height of the top surface of the bleeding water was also recorded.

[0041] Figure 2 shows the changes over time in the height of the top surface of the grout material, the top surface of the machine oil, and the top surface of the bleeding water (the vertical axis of the graph is based on a height of 300 mm). Figure 3 shows the condition immediately after the start of the test and the condition when bleeding water is generated. It was found that when bleeding water is generated, a thickness of 0.25 mm can be visually measured. It was also found that bubbles generated by degassing are visible. In particular, the unburned carbon, which has a low specific gravity and is contained in the grout material, adhered to the bubbles and floated to the top surface of the machine oil, making it easy to understand the degree of degassing. Furthermore, by layering machine oil on the top surface of the grout material, the grout material was not exposed to air, and degassing could be measured over a long period of time without being affected by environmental conditions.

[0042] <Test Example 1> Freshly mixed grout material B was filled into an acrylic tube erected on a stand, up to the reference line, through the opening at the top. Machine oil was then layered on top of grout material B (layer thickness 10 mm). Subsequently, changes in the height of the top surface of grout material B and the top surface of the machine oil were recorded every 15 minutes. Degassing was observed as time passed. Furthermore, bleeding did not occur even after time had elapsed.

[0043] <Test Example 2> The test was conducted in the same manner as in Test Example 1, except that after mixing grout material B, it was allowed to stand for 1 hour before being filled into the acrylic tube. Defoaming was observed as time passed. No bleeding occurred even after time had elapsed.

[0044] <Result> Figure 4 shows the changes over time in the height of the top surface of the grout material and the machine oil in Test Example 1 and Test Example 2. • Up to 8 hours after recording the change in height, there was a large change in the height of the top surface of the grout material. Given that the drying of the grout material was suppressed by the machine oil, that the grout material normally undergoes little auto-shrinkage up to 8 hours later, and that no bleeding occurred, it is thought that the change in the height of the grout material during this period was due to the effect of de-aeration. • In Test Example 2, the change in the height of the top surface of the grout material was smaller than in Test Example 1. In on-site construction, it is strongly presumed that allowing the grout material to stand for one hour after mixing, as in Test Example 2, will result in smaller volume changes of the grout material. After 8 hours, the height of the top surface of the grout material stabilized, whereas the height of the top surface of the machine oil did not stabilize and gradually decreased. This is thought to be because the moisture content in the grout material decreased as it hardened, and the machine oil was absorbed by the hardened grout material. [Industrial applicability]

[0045] This invention can be used in the construction of grout materials. [Explanation of Symbols]

[0046] 1...Container, 2...Grout material, 3...Laminating liquid (liquid), 4...Bleeding water.

Claims

1. A test method for determining the volume change of grout material, A liquid with a specific gravity lower than water and that is incompatible with water is layered on top of the unhardened grout material filled in a columnar container. A test method for recording the change over time of at least one of the following: the height position of the upper surface of the grout material, the height position of the upper or lower surface of the liquid, and the height position or thickness of the upper surface of the bleeding water in the event of bleeding.

2. The test method described in claim 1 is carried out, A test method comprising repeating the test method based on the results, by changing at least one of the following: the mixing time of the grout material, the resting time of the grout material, the amount of water added, and the materials of the grout material.

3. The container has a cylindrical shape in the part where the grout material is filled, The inner diameter of the cylindrical shape is 50 mm to 150 mm. The test method according to claim 1, wherein the height of the filled grout material is 297 mm to 303 mm.

4. The test method according to claim 1, wherein the grout material contains an expandable material that does not generate gas.

Citation Information

Patent Citations

  • Formwork structure

    JP7145809B2